Metal powder addition in submerged arc welds - Cheong, Fook Loy. (2009)
Study on the feasibility of metal powder addition in submerged arc welding (SAW) of steel was carried out and its effect on the deposition rate and mechanical properties of welds was evaluated. The principal objective of the work was to increase the deposition rate of SAW process without increasing the heat input. The experimental work was carried out in two stages: preliminary studies to evaluate the effect of powder addition on its recovery, weld bead geometry, and cooling rate for a number of heat inputs using bead-on-plate (BOP) welds. From these results the optimum welding conditions in terms of current, heat input, and powder feed rate were obtained. Using these optimum conditions, groove welds in 25mm thick low carbon steel plates were deposited and evaluated for cooling rates, mechanical properties and joint completion rate.